HISTORIOGRAPHY OF SOUTH AFRICAN SOCIAL WORK: CHALLENGING DOMINANT DISCOURSES - Smith, Linda (Social Work/Maatskaplike Werk, 2014)
The task of examining the origins and development of social work is fraught with competing narratives. In South Africa individualist, liberal, colonial, masculine and “white” discourses prevail. The dialectical-historical perspective, rather than chronological “progress”, shows how socio-political and economic dynamics are formative of societal conditions and of social work, which in turn has a role in shaping these dynamics. The fiction of purely historical records of progress and freedom of choice is challenged, and hegemonic and counter-hegemonic discourses uncovered. Social workers are urged to be engaged with the full complexity of events emerging from the class and race-based antagonisms of South African society.